Edukasi PHBS (Perilaku Hidup Bersih dan Sehat), dan Social/Physical Distancing sebagai Upaya Pencegahan Penularan Virus Corona (Covid-19) pada Keluarga Pra Sejahtera - Fitri Mailani; Rahmi Muthia; Emil Huriani; Sovia Susianty (Warta Pengabdian Andalas, 2020)
Entering the new normal era, some people think that the threat of Covid-19 is nothing to fear. But in reality the number of new cases of patients infected with Covid-19 is increasing. This proves that awareness of the Corona virus transmission still needs to be improved. Especially for pre-prosperous families whose access to information is limited. Limited health workers providing education to all levels of society are also an obstacle in the midst of this pandemic. The aim of this activity is to increase the knowledge of the underprivileged community about how to prevent the transmission of the Covid-19 virus. The method of implementing this activity is door-to-door education to underprivileged families living in the village of Sungai Buluh Selatan, Kabupaten Padang Pariaman, the majority of whom work as factory workers and daily laborers. Education was carried out using the media module/booklet and was carried out for three days, namely 1-3 July, 2020, to 32 pre-prosperous families who had been recommended by the head of the jorong. Education includes how to prevent the transmission of the Covid-19 virus, implement clean and healthy living habits, how to do physical/social distancing and how to use the right cloth masks, and make environmental disinfectants with cheap materials. The results of the evaluation show an increase in family understanding and motivation regarding the prevention of Covid-19 transmission. Continuous education is still very much needed, especially for underprivileged families whose access to information sources is limited.